EFFECTS OF SOYBEAN SEEDS ON HISTOLOGICAL STRUCTURE OF LIVER OF MALE RATS Rattus norvegicusTREATED WITH URANYL NITRATE - Al- Hilfy, Jabber; AL– Mehdawi, Ferial; Al-Kaisy, Kawkab (Iraqi Journal of Science, 2024)
Effects of Soybean and Uranyl nitrate on the histological structure in the rat liver were investigated. 32 prepubertal albino male rats were divided as fallows : G1, control, , G2, was given intragastrically 75mg / kg / b.w Uranyl nitrate, G3 was fed with 20% Soybean, and G4 was treated with both Uranyl nitrate and Soybean as in G2 and G4. Light microscope results showed a degenerative changes in different areas of liver tissue in (G2), these changes include: Pyknotic nuclei, vacuolation, infiltration of inflammatory cells, hypertrophy, sinusoidal enlargement and found spaces like cystic structures in attachment with nucleus of some cells. A normal appearance of liver tissue in some areas and degeneration of some cells, fatty infiltration and sinusoidal enlargement in other areas were observed in (G3), while in (G4) normal areas were observed with degenerative nuclei, sinusoidal enlargement and infiltration of some inflammatory cells in other areas. From these results it can be conclude that the treatment with Uranyl nitrate has a negative effect, and the active components of soybean may play an important role in the inhibition of these effects in liver cells.